2003
DOI: 10.1080/716100638
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Pre-B and Igm + B Cells in the Bone Marrow After Exposure to a Mixture of Herbicides

Abstract: This study determined alterations to bone marrow B-cell populations after in vivo exposure to a mixture containing the herbicides 3,4-dichloropropionanilide (propanil) and 2,4-dichlorophenoxyacetic acid (2,4-D) and compared them to the effects of exposure to the individual herbicides. Propanil and 2,4-D are postemergent herbicides that are sold commercially as a mixture. The individual herbicides or the mixture containing propanil and 2,4-D were administered intraperitoneally to C57Bl/6 female mice at doses fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…3,4-dichloropropionaniline is also a herbicide, and suppresses several to suppresses normal macrophage function (Ustyugova et al, 2007). A mixture containing the herbicides 3,4-dichloropropionanilide and 2,4-dichlorophenoxyacetic acid induce the Loss of pre-B and IgM(+) B cells in the bone marrow (de la Rosa et al, 2003). About the effect of paraquat on productivity of IgA IgG and IgM, there has not been enough information.…”
Section: Resultsmentioning
confidence: 99%
“…3,4-dichloropropionaniline is also a herbicide, and suppresses several to suppresses normal macrophage function (Ustyugova et al, 2007). A mixture containing the herbicides 3,4-dichloropropionanilide and 2,4-dichlorophenoxyacetic acid induce the Loss of pre-B and IgM(+) B cells in the bone marrow (de la Rosa et al, 2003). About the effect of paraquat on productivity of IgA IgG and IgM, there has not been enough information.…”
Section: Resultsmentioning
confidence: 99%
“…2,4-Dichlorophenoxyacetic acid (2,4-D) and 3,4-dichloropropionanalide (propanil) are commonly used herbicides marketed as a chemical mixture under the product names of NOX-D and Herbanil 368 (Meister and Sine, 2003). Previous research has demonstrated that 2,4-D and propanil are immunotoxic to the primary immune organs and to specific immune cell functions; however, the effects of an exposure to a mixture of these herbicides on an in vivo immune response has not been studied (Barnett and Gandy, 1989;Blakley, 1997;de la Rosa et al, 2003de la Rosa et al, , 2005. This study was performed to determine if exposure to these herbicides, either alone or as a mixture, altered the primary humoral immune response to the model bacterial vaccine, heatkilled Streptococcus pneumoniae (HKSP).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that exposure to either propanil or 2,4-D alone induced thymic atrophy and reduced the number of double positive (CD4 þ CD8 þ ) thymocytes (de la Rosa et al, 2005). In the bone marrow, exposure to either herbicide alone decreased the number of pre-B (B220 þ CD43 þ IgM low ) cells and IgM þ B (B220 þ CD43-IgM hi ) cells (de la Rosa et al, 2003). However, exposure to the mixture of propanil and 2,4-D caused greater-than-additive decreases in the same cell populations in the thymus and bone marrow, suggesting that interactions of the mixture increased the toxicity of the individual chemicals (de la Rosa et al, 2003Rosa et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…propanil exposure at the lowest studied dose of 50 mg/kg decreased the number of murine pre-B cells in the bone marrow (50% of control) 7 days post-exposure (de la Rosa et al, 2003). Immature IgM + B cells were also decreased in number (50% of control) at a dose of 150 mg/kg 7 days post-exposure (de la Rosa et al, 2003). Fourteen days after propanil exposure the pre-B and immature IgM + B cell populations had returned to control levels.…”
Section: B Cell Toxicity and The Humoral Immune Responsementioning
confidence: 99%